The Baffin Bay Region During the Last Interglaciation: Evidence from Northwest Greenland - Funder, Svend (Géographie physique et Quaternaire, 1989)
ABSTRACTCoastal sections in the Thule area, northwest Greenland, provide a record of last interglacial glacial and océanographie events on the northern perimeter of Baffin Bay. The record is dated by a combination of thermoluminescence and 14C dating; local and regional correlation is provided by amino acid analyses of mollusc shells, and periods of penetration by warm subarctic water have been identified by their foraminifera and mollusc faunas. Subarctic water reached the area on three occasions : during the Holocene, and in the Early and Late Sangamonian. Maximum, although restricted, ice coverage for the last interglacial/glacial cycle was attained during Middle Sangamonian times, and a smaller advance took place in the Late Wisconsinan. In between ice coverage was similar to the present, or smaller. The record provides a link between events in Arctic Canada and northern Greenland, and shows that in this large region there was a causal relationship between océanographie change and glaciation.